Learning from financial crisis: the experience of Nordic banks - Tom Berglund; Mikko Mäkinen (Bank of Finland, 2016)
To study whether banks retain their lessons from the experience of a severe financial crisis, we examine the effects of the systemic banking crisis of the early 1990s in three Nordic countries (Finland, Norway, and Sweden). While this crisis largely bypassed the rest of Europe, we hypothesize that banks in the three affected Nordic countries took their crisis experiences to heart and as a result outperformed other European banks during the 2008 global financial crisis. Based on a large panel data set of Nordic and European banks for the period 1994–2010, our findings support our main hypothesis that the Nordic banks learned from the 1990s crisis and adjusted their business models accordingly. Our descriptive analysis of Nordic banks finds evidence of "lessons learned" in such precautions as robust capital cushions, improvements in management efficiency and higher credit quality demands relative to the rest of Europe.
URN:NBN:fi:bof-201612141531
Keywords: G01; G21; G34; 330